Community Social Movement Through Digital Media as a Response to the Covid-19 Pandemic in Surabaya, East Java - Kamaruddin Salim; Tia Azriani (Indonesian Journal of Digital Society, 2020)
Surabaya is one of the cities in Indonesia which is currently facing the Covid-19 pandemic. The number of positive sufferers of Covid 19 in Surabaya is the highest in East Java Province. Efforts to deal with the Covid-19 pandemic The Surabaya City Government has implemented a Large-Scale Social Restriction (PSBB) regulation, on April 28-May 11 2020, and the second stage from May 11-25, 2020, through various types of information media. PSBB regulations have been conveyed to the public. This has reaped various responses from the public regarding efforts to deal with the Covid-19 outbreak, there are people both individually and collectively who accept and obey regulations from the Surabaya City Government, but there is Covid-19 19. The results of the study show that there are active community groups and there are also community groups who are passive in supporting efforts to prevent the Covid-19 pandemic in the City of Surabaya. For community groups who play an active role in responding to the Covid-19 pandemic, there are various types of social movements that are being carried out. This social movement was carried out collectively to help people affected by the Covid-19 pandemic Keywords : Social movement, digital media, Covid-19 pandemic